Pengaruh Motivasi Kerja Dan Kompetensi Terhadap Kinerja Karyawan Dinas Perumahan Kawasan Permukiman Dan Pertanahan Kabupaten Cilacap - Dian Rachmawati Prasetyaningrum; Enas Enas; Irma Bastaman (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
Regarding the implementation of employee performance of the Housing, Residential Areas and Land Agency of Cilacap Regency, it is marked by the fact that there are still delays in completing tasks and work for employees. This results in delays in providing reports on their tasks and work to the leadership, and low employee awareness of the tasks/obligations that are their responsibility and inadequate employee abilities for the tasks assigned to the work apparatus. The formulation of the problem proposed in this study includes: 1. How does work motivation affect employee performance? 2. How does competence affect employee performance? 3. How much influence do work motivation and competence have on employee performance? The method used in this study uses a quantitative method. To analyze it, using statistical correlation and multiple regression test data analysis using the SPSS program. The results of the analysis prove that motivation has a positive and significant effect on employee performance. This means that the higher the motivation, the higher the employee performance, this is evidenced by the results of the analysis of the contribution data of X1 to Y with a coefficient of determination (r2) of 0.407 (40.7%) and then competence has a positive and significant effect on employee performance. This means that the higher the competence, the higher the employee performance, this is evidenced by the results of the analysis of the contribution data of X2 to Y with a coefficient of determination (r2) of 0.453 (45.3%). Furthermore, motivation and competence have a positive and significant effect on employee performance. This means that if there is motivation and competence, then employee performance will also increase. This is evidenced by the results of the analysis which states the contribution of variables X1 and X2 to Y with a correlation (r) of 0.722. If consulted with the table of interpretation values ​​r, then the level of relationship between X1 and X2 to Y is included in the fairly strong category. The coefficient of determination (r2) is 0.521 which means that motivation and competence affect employee performance by 52.1% while the remaining 47.9% is influenced by other factors outside that are not studied.